Guides for Cardiopulmonary Resuscitation - Escalante-Kanashiro, Raffo (2010)
The objective of the present article is the approach of 2010 ECC & CPR Guidelines and their principal modifications. Guidelines are the result of scientific evidence and clinical research that support statements and new recommendations. Some important changes in 2010 present in the Chain of Survival which includes aspects of Postresuscitation Care1,2. CPR Guidelines were published and uploaded on-line (Resuscitation and Circulation publication) in October 18th, 20109,10. One of the most important training and learning strategies is the dissemination of concepts from ILCOR CPR and ECC Guidelines which had extended into ERC and AHA. This has allowed the medical personnel to treat patients victims of cardiac arrest or cardiac emergency efficiently. We are convinced that interactive methodology and clinical simulation are essential for training and learning. We cannot know cardiopulmonary resuscitation without discussion of science and performance of lively clinical scenery cases for each of the main topics in CPR and ECC.